Disiplin, Motivasi Berprestasi, dan Tanggung Jawab serta Hubungannya dengan Perolehan Belajar Tematik - Fathoni, Fahmi; Aunurrahman, Aunurrahman; Hartoyo, Agung (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The purpose of this research are to characterize the following relationships: that between learning gains and accomplishment motivation, discipline, and responsibility; that relationship between these relationships and learning gains; and that between the combined predictor factors and the criterion variable, as a percentage. This study, which was carried out at SD Mujahidin Pontianak with a sample of 183 kids, combined a descriptive method and a quantitative approach. Questionsnaires were used in the data collection process. Many strategies for correlation were employed in data analysis. The findings revealed a favorable and substantial connection between : 1) discipline and learning gain (r of 0.967); 2) achievement motivation and learning gain (r of 0.930); and 3) responsibility and thematic learning gain (r of 0.971). Additionally, the three predictor variables—discipline (X1) at 0.32%, achievement motivation (X2) at 0.30%, and responsibility (X3) at 0.33%—contributed 0.95% to the criterion variable. With a contribution of 0.33%, the accountability variable (X3) is the largest factor in learning gain.